Archimedes filled water to the top of a conic cup of radius R and height h . He then dropped a golden spherical ball of radius r into the cup such that the ball was perfectly inscribed within the cone and its water surface, making the same amount of water spill over. Then he took out the the golden ball and poured out half of the full cone's volume. The resulting height of the water was 2 h .
"Eureka! Eureka!" He exclaimed as he had already known the dimension ratios of these shapes.
Given that R is an integer and h , r are coprime integers, compute R + h + r .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This part could be clarified further
After calculating the replaced volume, he removed the golden ball from the cone. Out of the remaining water, he also poured out half of the full cone's volume. Then he noticed that the water level had become half of its original height.
Are you saying that "there is exactly half of the full cone's volume left behind" or that "he pours out half of the full cone volume, and then the water level is half"?
Log in to reply
Actually, this was not my original message. I'll revise it again. Thanks for pointing out.
What does poured out mean ? Does that mean when Archimedes grab out the ball, the half of the cone got caught in his hand and got thrown away ?
Log in to reply
He poured out half of the full come volume, not the remaining one.
V c o n e = 3 π R 2 h V b a l l = 3 4 π r 3 The volume of the ball, and another half cone are spilled, and a 1/8 cone's volume is left: V c o n e − V b a l l − 2 1 V c o n e = 8 1 V c o n e 3 V c o n e = 8 V b a l l π R 2 h = 3 3 2 π r 3 Multiply both sides by π R 3 3 : 3 R h = 3 2 ( R r ) 3 If the ball is touching the cone and the water surface, let β be the angle between the plane of the water surface and a line from the edge to the ball's centre. The water surface and a line from edge to apex make an angle 2β. So we can show that R r = tan β then R h = tan 2 β . 3 tan 2 β = 3 2 tan 3 β
Using the double angle formula tan 2 β = 1 − tan 2 β 2 tan β , and setting x = tan β we get 1 − x 2 6 x = 3 2 x 3 which simplifies to 1 6 x 4 − 1 6 x 2 + 3 = 0 so that x 2 = 2 × 1 6 1 6 ± 1 6 2 − 4 × 3 × 1 6 = 4 2 ± 1 so, knowing that x > 0 , either x = 2 1 or x = 2 1 3 .
For x = 2 1 3 , R r is not rational, so this will not lead to a solution of the problem.
For x = 2 1 we get R r = 2 1 and tan 2 β = R h = 3 4 . So here we get the ratio r : R : h = 3 ÷ 6 ÷ 8 which are coprime, hence the answer is R + h + r = 1 7
Problem Loading...
Note Loading...
Set Loading...
The volume of the cone = 3 π R 2 h .
The volume of the sphere = 3 4 π r 3 .
With half of the original height, the cone's radius will be halved as well because within a conic 2-D plane, they are two similar triangles. Hence, the volume of the remaining water = 3 π ( 2 R ) 2 ( 2 h ) = 8 1 ( 3 π R 2 h ) .
The remaining water is 8 1 of the full cone's volume V , and when added this to the sphere's volume, it will equal to half of the full cone's volume as half of the water would be poured out to result in these volumes.
Therefore, sphere's volume = ( 2 1 − 8 1 ) V = ( 8 3 ) V .
Now substituting in terms of R , h , r variables:
3 4 π r 3 = ( 8 3 ) 3 π R 2 h
r 3 = ( 3 2 3 ) R 2 h
Now we have to find the radius of the inscribed sphere within the cone as a circle inscribed in a triangle:
From the image above, the radius r is perpendicular to all three tangents, and so the area of the whole triangle equals the sum of three triangles with height r = ( 2 1 ) r ( 2 R + 2 R 2 + h 2 ) .
But we know that this triangle has base 2 R and height h .
Hence, R h = r ( R + R 2 + h 2 ) . r = R + R 2 + h 2 R h = 1 + 1 + ( R h ) 2 h .
Substituting the term into the previous equation:
r 3 = ( 1 + 1 + ( R h ) 2 h ) 3 = ( 3 2 3 ) R 2 h .
Suppose R h = k ; h = R k .
( 1 + 1 + k 2 R k ) 3 = ( 3 2 3 ) R 2 ( R k ) .
( 1 + 1 + k 2 k ) 3 = ( 3 2 3 ) k .
( 1 + 1 + k 2 ) 3 k 2 = 3 2 3 .
Then let x = 1 + k 2 :
( 1 + x ) 3 x 2 − 1 = 3 2 3 .
x 2 − 1 = ( 3 2 3 ) ( ( 1 + x ) 3 )
3 2 ( x + 1 ) ( x − 1 ) = 3 ( x + 1 ) 3
0 = ( x + 1 ) ( 3 ( x 2 + 2 x + 1 ) − 3 2 ( x − 1 ) )
0 = ( x + 1 ) ( 3 x 2 − 2 6 x + 3 5 )
0 = ( x + 1 ) ( 3 x − 5 ) ( x − 7 )
x can't be − 1 because the square root value is positive. Therefore, x = 3 5 or x = 7 .
If x = 7 , 1 + k 2 = 7 . k = 7 2 − 1 = 4 8 = 4 3 .
If x = 3 5 ), 1 + k 2 = 3 5 ). k = ( 3 5 ) 2 − 1 = 3 4 .
Since both R and h are integers, its ratio must be rational number. Thus, k can't be 4 3 .
Hence, h = 3 4 R .
Plugging in this term into the original equation for r :
r = 1 + 1 + k 2 h = 1 + 1 + ( 3 4 ) 2 h = 3 8 h .
Thus, 8 r = 3 h , and since they are co-prime, r = 3 ; h = 8 . That makes R = 2 r = 6 .
As a result, R + h + r = 6 + 8 + 3 = 1 7 .